A Video Intervention to Increase Organ Donor Registration at the Department of Motorized Vehicles - DuBay, Derek (Transplantation, 2020)
BACKGROUND. The goal of this study was to increase organ donor registrations at the Department of Motorized Vehicles (DMV) via utilization of a sustainable, low-cost, African American-centric organ donation educational video. Results from previous studies provided a framework to generate a 10-minute video that featured registered organ donors, deceased donor families, and transplant recipients. METHODS. The video was presented via an interrupted time series design (repeating on 2 months, off 2 months) on TVs placed in 6 regional DMVs. 162,387 patrons visited the DMVs during the 12-month study. RESULTS. Increases in organ donor registration were consistently observed in each DMV while the video was on compared to off [mean = +2.3% (range +1.98% to +3.35%); P < 0.0001]. Multivariable analysis demonstrated that females (OR 1.29; 95% CI 1.26 – 1.31) younger age (OR 0.982/year; 95% CI 0.982–0.983), and the video intervention (OR 1.09; 95% CI 1.07–1.12) were significantly associated with increased registration; while compared with Caucasian race, African American race was not, (OR 0.22; 95% CI 0.22–0.23). There was no video-dependent effect on registration between Caucasians and African Americans (P = 0.62). Exit interviews demonstrated only 16% of patrons could identify the key message in the video (becoming a registered organ donor). CONCLUSIONS. An educational video promoting organ donation resulted in increased organ donor registration at the DMV. The intervention was equally effective in African Americans and Caucasians. Future efforts should focus upon target-specific messaging and patron consumption of the educational video.